Event conceptualization by early Dutch-German bilinguals: insights from linguistic and eye-tracking data* - Flecken, Monique (Bilingualism, 2011)
This experimental study investigates event construal by early Dutch-German bilinguals, as reflected in their oral depiction of everyday events shown in video clips. The starting point is the finding that the expression of an aspectual perspective (progressive aspect), and its consequences for event construal, is dependent on the extent to which means are grammaticalized, as in English (e.g., progressive aspect) or not, as in German (von Stutterheim & Carroll, 2006). The present study shows that although speakers of Dutch and German have comparable means to mark this aspectual concept, at a first glance at least, they differ markedly both in the contexts as well as in the extent to which this aspectual perspective is selected, being highly frequent in specific contexts in Dutch, but not in German. The present experimental study investigates factors that lead to the use of progressive aspect by early bilinguals, using video clips (with different types of events varied along specific dimensions on a systematic basis). The study includes recordings of eye movements, and examines how far an aspectual perspective drives allocation of attention during information intake while viewing the stimulus material, both for and while speaking. Although the bilinguals have acquired the means to express progressive aspect in Dutch, their use shows a pattern that differs from monolingual Dutch speakers. Interestingly, these differences are reflected in different patterns in the direction of attention (eye movements) when verbalizing information on events.
Erstmals online veröffentlicht am 23. September 2010
Gesehen am 18.01.2023